Akuntansi Syariah dalam Perspektif Sejarah - Firyal Aufa Annisa; Muhammad Ichsan Adnan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Sharia Accounting is a discipline grounded in Islamic principles derived from the Qur'an and Hadith, encompassing core values such as justice, transparency, and accountability. This study aims to analyze the historical development of Sharia accounting by reviewing existing literature and examining its practical application within the context of the Islamic economic system. The research employs a literature analysis method, including a comprehensive review of relevant documents, scholarly articles, and books that discuss Sharia accounting from the early Islamic period to the modern era. The findings indicate that Sharia accounting has undergone significant evolution, beginning with the accounting practices during the time of the Prophet Muhammad, which emphasized honesty and transparency in financial transactions. Over time, Sharia accounting has adapted to contemporary economic demands, including the integration of information technology in the preparation of Sharia-compliant financial reports. Furthermore, the study identifies several ongoing challenges in the implementation of Sharia accounting. Nevertheless, there is considerable potential for further development, particularly in enhancing public trust in Islamic financial institutions. This research is expected to contribute to a deeper understanding of Sharia accounting and its application in the context of the global economy.